THREE-DIMENSIONAL INTERACTIVE VISUALIZATION PATHOLOGICAL ACTIVITY BRAIN - O. P. Vysotsky; T. S. Bobrova; D. I. Zmitrukevich; G. I. Ovsyankina; A. A. Boriskevich; M. V. Davydov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The article examines patterns of abnormal brain activity of human type «spike» and type «sharp wave». The program automatically detect the type of «Spike» and patterns such as «sharp wave»based on wavelet transform and mathematical package MATLAB. It creates an interactive three-dimensional visualization of the pathological activity of the «spike» of the human brain and the type of «sharp wave».